An Analysis of Student’s Motivation in Reading Procedure Text at the Second Grade of SMA Negeri 1 Palopo - Mufliha, Wilda Nur; Munir, Munir; Tahir, Muhammad (State University of Makassar, 2024)
This study discusses the motivation of students in reading procedure text in class II at SMA Negeri 1 Palopo. This research is important because by analyzing students' motivation they can prepare steps to improve students' reading skills. The data analysis technique that the researcher did was descriptive quantitative. Questionnaires were used to collect data. The results showed that there was a significant analysis of student learning motivation. It can be shown that from 36 students in reading procedure text there are 13 students (85%-100%) in the strongly positive category, 17 students (69%-84%) in the positive category, 4 students (53%-68%) in the positive category. moderate, and 2 students (37%-52%) in the negative category.Keywords: Analysis Motivation, Reading Skills.